Reliability and validity of the transcultural self-efficacy tool questionnaire (Greek version) - Sarafis, Pavlos; Igoumenidis, Michael; Tzavara, Chara; Malliarou, Maria (My University, 2014)
Background and Purpose: This study aimed to investigate the psychometric characteristics of the Transcultural Self-Efficacy Tool (TSET). Methods: The translated questionnaire was distributed to 250 nurses and 150 student nurses. Internal consistency was determined and convergent validity was examined. The structure of the questionnaire was investigated using factor analysis. Results: The internal consistency coefficient for all subscales was acceptable and more than .70. Cronbach's alpha was .91 for affective and self-awareness subscales and .85 for recognition and advocation. Six factors were revealed with eigenvalues of more than 1 and accounted for 60% of the total variance. Conclusions: The factorial composition of the TSET continues to be consistent with the underlying theoretical framework and the related literature. The Greek version of TSET was found to possess good reliability and validity.
Keywords: Cultural competence; Greece; Instrument evaluation; Nurses; Psychometric properties; Test